Assessment of the Attitude of Health Care Professionals towards Diabetes Care in Mukalla, Yemen - Salmeen Doagel Babelgaith; Saeed Alfadly; Mohd Baidi Bahari (Intelektual Pustaka Media Utama, 2013)
Diabetes mellitus is a major public health concern and considered as a condition that leads to increased morbidity and mortality worldwide. The prevalence of diabetes in Yemen has been recently increased. The aim of this study was to evaluate the attitudes of health care professionals towards diabetes (HCPs) care in Mukalla , Yemen . The cross sectional study was conducted among health care professionals in Mukalla city, Yemen. The diabetes attitudes questionnaire was administered to 73 health care professionals (Doctors , pharmacists and nurses ) in Mukalla , Yemen in 2009. The data were analyzed descriptively and the inferential Kruskal -Wallis test was also used. This study found that healthcare professionals have relatively adequate attitudes toward diabetes. Doctors have higher attitudes score toward the seriousness of diabetes than other healthcare professional groups (pharmacists and nurses), and nurses showed the lowest attitude score among healthcare professional groups. Therefore, nurses and pharmacists should receive more education programmes regarding diabetes care. DOI: http://dx.doi.org/10.11591/ijphs.v2i4.3842